Pola Komunikasi Keluarga dan Pengasuhan Ramah Anak Sebagai Upaya Membentuk Kepribadian Anak - Khoirun Ni'mah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2018)
One aspect that can not be separated from the process of child development is related to parenting. A good parenting process enables the child to grow and develop optimally. Using qualitative research approach, this research aims to observe, understand, and analyze how the application of the communication patterns done by several fami- lies, such as the efforts of parents to inculcate of cultural values that support of the child’s personality development. In addition, this study also aims to develop child friendly parenting models that contribute to the child’s personality development. In this case, the authors argue that positive and negative of child’s personality depends on values that have been instilled through family communication and parenting model. All parties, such as parents, families, communities, and governments have a role and responsibility to create a process and a good parenting environment for children.